Stress and Tinnitus; Transcutaneous Auricular Vagal Nerve Stimulation Attenuates Tinnitus-Triggered Stress Reaction - Ylikoski, Jukka; Markkanen, Marika; Pirvola, Ulla; Lehtimäki, Jarmo Antero; Ylikoski, Matti; Jing, Zou; Sinkkonen, Saku T.; Mäkitie, Antti (Frontiers in Psychology, 2020)
Tinnitus can become a strong stressor for some individuals, leading to imbalance of the autonomous nervous system with reduction of the parasympathetic activity. It can manifest itself as sleep disturbances, anxiety and even depression. This condition can be reversed by bioelectrical vagal nerve stimulation (VNS). Conventional invasive VNS is an approved treatment for epilepsy and depression. Transcutaneous VNS (taVNS) stimulating the auricular branch of the vagus nerve (ABVN) has been shown to activate the vagal pathways similarly as an implanted VNS. Therefore, taVNS might also be a therapeutic alternative in such health conditions as tinnitus-related mental stress (TRMS). This retrospective study reports in 171 TRMS patients the clinical features, psychophysiological characteristics, and results of the heart rate variability (HRV) tests before and after test-taVNS. This study also reports the therapy outcomes of 113 TRMS patients treated with taVNS, in addition to standard tinnitus therapy. Diagnostic tinnitus and hearing profiles were defined. To detect possible cardiac adverse effects, a test-taVNS with heart rate monitoring and pre- and post-stimulation HRV tests were performed. A daily taVNS home-therapy was prescribed thereafter. To assess the therapeutic usefulness of taVNS, one-year follow-up outcomes were studied. Results of the HRV tests were retrospectively analyzed and correlated to diagnostic data. The large majority of patients with TRMS suffer from associated symptoms such as sleep disturbances and anxiety. Baseline HRV data of 171 patients showed that more than three quarters of them had increased sympathetic activity before the test taVNS. The test taVNS shifted the mean values of different HRV parameters towards increased parasympathetic activity in about 80 % of patients. The test-taVNS did not cause any cardiac or other side effects. No significant adverse effects were reported in follow-up questionnaires TRMS is an example of a stress condition in which patients may benefit from taVNS. As revealed by HRV, the test-taVNS improved parasympathetic function, most efficiently in patients with a low starting HRV level. Our tinnitus treatment program, including taVNS, effectively alleviated tinnitus stress and handicap. For wider clinical use, there is a great need for more knowledge about the optimal methodology and parameters of taVNS.